Analısıs Aspek Gramatikal pada Lırık Lagu Muhasabah Cinta Karya Grup Musik Nasyid Edcoustic - Saraswati, Saraswati (Universitas Mathla'ul Anwar Banten, 2021)
This study analyzes the lyrics of the song Muhasabah Cinta, a song from the religious music group by edCoustic, which is a nasyid music group in Indonesia from Bandung which carries the concept of religious humanist music. This group takes the path of progressive pop music with an acoustic touch. Muhasabah Cinta is a reflection of our love for God and contemplation of the afterlife. The song Muhasabah Cinta is able to express the religious messages contained in the lyrics. This song will be analyzed grammatically by classifying grammatical forms. The findings of the grammatical aspect include 35 references, which consist of 22 single pronominal I form references, 3 forms of I, 10 single pronominal II personal references consisting of 4 forms of -Mu, Kau forms as many as 3, and the form of God and Divine 3. There are 2 temporal (time) demonstrative references, namely the present form and so far. There are 2 demonstrative references (places) with this and that form. There are 12 substitution findings, 11 ellipsis findings, and 4 conjunctions. This study is a qualitative research using linguistic data. The data is in the form of a description of words in context. The method used is the listening method and the note-taking technique with content analysis.